The prevalence and associated factors of overweight/obesity and abdominal obesity in South-eastern of Iran: a cross-sectional study based on Rafsanjan cohort study - Tabandeh Sadeghi; Narjes Soltani; Zahra Jamali; Fatemeh Ayoobi; Parvin Khalili; Ali Shamsizadeh; Mostafa Nasirzadeh; Ali Esmaeili‑Nadimi; Carlo La Vecchia; Zahra Jalali (BMC, 2023)
Abstract Background Obesity has become a major health issue in both high and middle-income countries, increasing the risk of cardiovascular diseases and all-cause mortality. Risk of obesity is related to both unchangeable factors such as genetics and gender, and modifiable lifestyle factors. Most importantly, finding the major modifiable lifestyle factors which contribute to obesity may provide valuable benefits to every society. This study aimed to determine the association of demographic and lifestyle parameters with overweight/obesity and abdominal obesity in a population of Iranian adults. Methods In this cross-sectional study, adult participants of Rafsanjan Cohort Study (RCS) (as one of the district areas of the PERSIAN cohort (Prospective Epidemiological Research Studies in IrAN) included the study population. RCS is a population-based prospective cohort of men and women aged 35-70 years, launched in August 2015. Individuals were recruited from four urban and suburban areas of Rafsanjan, south-eastern of Iran. Trained experts interviewed each participant and completed the related questionnaires about his/her socioeconomic status, demography, anthropometric features, personal habits, physical activity and medical history. Multinomial logistic regression models were used to examine the relationships between overweight/obesity/abdominal obesity and associated factors. Results From 9980 participants, 1974 (42.42%) males and 2115 (39.70%) females were overweight, 784 (16.85%) males, 2223 (41.73%) females were obese and 1895 (40.73%) males and 989 (18.57%) females were normal weight. Also, 832 (17.9%) males and 4548 (85.4%) females had abdominal obesity and 3819 (82.1%) males and 778 (14.6%) females didn't have abdominal obesity. Based on the adjusted multiple logistic regression, overweight/obesity (BMI > 25) was associated with age > 45, female gender, education ≥ 13 years, heavy physical activity, wealth status index (WSI), alcohol consumption, current cigarette smoking and opium consumption compared to reference group. Also, odds of abdominal obesity displayed a significant association with age > 45, female gender, education > 5 years, physical activity, WSI, current cigarette smoking, alcohol and opium consumption compared to reference group. Conclusions Our results recommend local public health strategies that promote training the society on the health benefits of avoiding alcohol, getting more physical exercise and gaining more personal education on the health-threatening lifestyle.